Sustainable Intensification of Dairy Production Indonesia (SIDPI project) - Vries, Marion de (2017)
Dairy production in Indonesia cannot sustainably keep up with the growing demand for dairy. The goal of the SIDPI project is to "sustainably increase farmer incomes and improve livelihoods in smallholder dairy production systems in Indonesia." The project began in April 2016 and is scheduled to conclude in March of 2019. The presentation discusses activities and research done by the project so far.